Substance-based medical devices made of natural substances: An opportunity for therapeutic innovation - Giovagnoni, Emiliano (Frontiers in Drug Safety and Regulation, 2022)
The approval of EU Regulation 2017/745 has created a regulatory framework capable of consolidating an entire category of therapeutic products, that of Substance-based Medical Devices. The Regulation creates the conditions required to promote innovation in therapeutics, both for the so-called “minor illnesses” as well as for important “unmet medical needs”. At the same time, it significantly raises the standards for evaluating their efficacy and safety. Among the different kinds of Substance-based Medical Devices, those made of natural complex substances offer a special opportunity. In this new regulatory context, natural substances can be made available to the patient within an “evidence-based” context, guided by the principles of Systems Biology and Systems Medicine, and under the control of the healthcare sector. Substance-based Medical Devices are already an important product in the European therapeutic market and will likely play an increasing role in the years to come.